The effects of electronic cigarette use patterns on health-related symptom burden and quality of life: analysis of US prospective longitudinal cohort study data - Cao, Yue; Zhang, Xuxi; Fearon, Ian M.; Li, Jiaxuan; Chen, Xi; Xiong, Yuming; Zheng, Fangzhen; Zhang, Jianqiang; Sun, Xinying; Liu, Xiaona (Frontiers in Public Health, 2024)
ObjectiveThis study aimed to examine the association between e-cigarette (EC) use patterns and health-related symptoms (fatigue, pain, and emotional problems) as well as general quality of life (QoL).MethodsData were analyzed from 7,225 adults across Waves 1–6 of the US Population Assessment of Tobacco and Health (PATH) study. Current combustible cigarette (CC) or EC use patterns included dual CC/EC use, exclusive EC use, non-current use of CC or EC, and exclusive CC smoking. Multivariate linear mixed-effects models were used to investigate longitudinal associations between EC use patterns, and symptom burdens/QoL scores.ResultsThose who were not currently smoking or vaping reported the lowest fatigue, pain, and emotional problems, and the best QoL, among the four groups (all p < 0.001). Compared to exclusive CC smoking, exclusive EC use was associated with a significant decrease of 0.065 units in average fatigue (95% confidence interval [CI]: −0.121, −0.009), of 0.206 units in average pain (95% CI: −0.355, −0.058), and of 0.103 units in average QoL scores (95% CI: −0.155, −0.051), with emotional problems similar over time.ConclusionExclusive EC users had less health-related symptoms and better QoL than those who were exclusive CC smokers. This should be taken into account when assessing the harm reduction potential of ECs.